Future direction of the electromyography based method to evaluate muscle fatigue - Jamaluddin, Nurul Fauzani; Ahmad, Siti Anom; Mohd Noor, Samsul Bahari; Wan Hasan, Wan Zuha (IEEE, 2014)
Fatigue detection through electromyography analysis has been in use since 1912 when it was discovered by H. Piper. Until now, there has been much research on muscle fatigue through electromyography, both invasively and non-invasively. There are evolutions of the electromyography based approach to detect fatigue in various aspects including methodology, analysis, application and the evaluation of fatigue itself. This paper intends to provide a brief review of previous research as this will help beginning researcher to find further direction in this research area.